Analisis Sektor Industri Pertanian pada Model CAPM - Andreas Kiky (Ultima Management : Jurnal Ilmu Manajemen, 2015)
The most popular Asset Pricing that has been known for long time was CAPM. This model offers very simple approach and strong fundamental theory for financial literature. Base of previous research using time-series data, this model show very good explanation in explain variation of portfolio return. Aim of this research is to find some pattern in different industrial sector, especially agriculture sector. Keywords: CAPM, Empirical Evidence, Abnormal Return, Stock Return